RRESPONSE OF THE KRŠKO NUCLEAR POWER PLANT COINTAINMENT TO THE LOSS OF COOLANT ACCIDENT IN COMPUTER CODE APROS 6 - Jure Jazbinšek; Luka Štrubelj; Ivica Bašić (Journal of Energy Technology, 2024)
Containment is a combination of a steel shell and concrete shield building enclosure, completely surrounding a nuclear reactor, designed to prevent the release of radioactive material in the event of an accident. The NEK (Krško Nuclear Power Plant) reactor containment building nodalization in APROS 6 computer code has been developed based on the plant’s available documents and GOTHIC nodalization. The heat structure’s data are based on USAR (Updated Safety Analyses Report) Chapter 6 passive heat structures. In all other aspects, realistic calculations based on containment geometry have been performed except for the interior concrete, which has been explicitly calculated.An original containment nodalization based on 10 control volumes is proposed, taking into account the containment layout (well‐defined physical boundaries and corresponding communication openings) and accident behaviour. The nodalization is suitable for containment thermal‐hydraulic modelling according to design basis accidents. In the end, APROS nodalization is prepared based on the same 10‐volume nodalization, for which annulus‐volume is also included in the model, connecting the reactor building to the environment. The containment model was tested for transient response for conditions, which occur in a Double‐Ended Hot Leg Guillotine Break accident.